2021
DOI: 10.3390/vaccines9020154
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review about Different Vaccines against Classical Swine Fever Virus and Their Repercussions in Endemic Regions

Abstract: Classical swine fever (CSF) is, without any doubt, one of the most devasting viral infectious diseases affecting the members of Suidae family, which causes a severe impact on the global economy. The reemergence of CSF virus (CSFV) in several countries in America, Asia, and sporadic outbreaks in Europe, sheds light about the serious concern that a potential global reemergence of this disease represents. The negative aspects related with the application of mass stamping out policies, including elevated costs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 220 publications
0
41
0
1
Order By: Relevance
“…However, until the differentiation of CSFV from BVDV as distinct species, their vast differences in virulence and destructive implications for the pig industry were not appreciated. Whereas BVDV infection poses a lesser threat without restriction for herd movement, CSFV can spread rapidly in pigs and cause high mortality, requiring stringent sanitary protocols, restriction of movement/export, vaccinations, and culling of herds [ 56 , 57 ]. While there is no evidence for a host–species demarcation in PBV, our results provide a solid future basis for determining whether certain strains of this genus are linked to specific clinical condition in a given host.…”
Section: Discussionmentioning
confidence: 99%
“…However, until the differentiation of CSFV from BVDV as distinct species, their vast differences in virulence and destructive implications for the pig industry were not appreciated. Whereas BVDV infection poses a lesser threat without restriction for herd movement, CSFV can spread rapidly in pigs and cause high mortality, requiring stringent sanitary protocols, restriction of movement/export, vaccinations, and culling of herds [ 56 , 57 ]. While there is no evidence for a host–species demarcation in PBV, our results provide a solid future basis for determining whether certain strains of this genus are linked to specific clinical condition in a given host.…”
Section: Discussionmentioning
confidence: 99%
“…The control and eradication of CSF at a global level continues to be a challenge in animal health [ 1 , 2 , 25 ]. Vaccination remains the most feasible strategy to achieve this goal [ 3 , 26 , 27 ]. However, eradication policies have not always been based on vaccination, but rather on strict serological surveillance and stamping out, which has proved costly and inadequate from an ethical and animal welfare standpoint [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, prophylactic vaccination is still the primary strategy for preventing and controlling CSF in CSF-endemic regions. Traditional CSF live attenuated vaccines (LAVs) strains, such as C-strain, LPC strain, LK-VNIVViM strain, GPE-strain, Thiverval strain, and PAV-250 strain, could provide an effective, rapid, and solid immune protection against CSFV infection and have been widely used to fight CSF [26]. Although traditional LAVs are effective and safe, they lack a serological concept of differentiating infected from vaccinated animals (DIVA).…”
Section: Introductionmentioning
confidence: 99%
“…Holinka et al [27] reported that FlagT4Gv, a live attenuated marker vaccine, could induce protection against challenge with virulent CSFV as early as three days post-vaccination and an increase of IFN-α three days after FlagT4Gv vaccination might play an important role in the immune protection, which meant that a novel CSF LAV with DIVA capabilities was a good choice for CSF control. Additionally, in recent years, novel subunit marker vaccines based on the CSFV E2 protein have been developed for alternative options against CSF [26]. For example, a commercial CSF marker vaccine TWJ-E2 ® (Tecon Bio-technology Co., Ltd., Urumqi, China), containing a baculovirus-expressed E2 glycoprotein of vaccine C-strain of genotype 1.1, was reported to provide complete protection to pigs against lethal challenge with virulent Shimen strain of genotype 1.1 and heterologous strains of genotype 2 [28,29].…”
Section: Introductionmentioning
confidence: 99%